Impact of series FACTS controllers on distance protection-A review - Singh S.; Vishwakarma D.N. (My University, 2025)
This paper presents a bibliographical survey and review of research and development in the field of impact of series FACTS (Flexible alternating current transmission system) devices on distance protection of transmission line. FACTS controllers are capable of controlling power flows, reactive power, damping of power system oscillations, transmission voltage and enhancing the usable capacity of existing transmission lines. It can control the power flow by means of controlling impedance, phase angle or series injection of appropriate voltage. Distance relays are widely used as main and back-up protection for transmission lines and are based on the electrical measure of distance along a transmission line to a fault. Its operation is dependent on the ratio of voltage and current, which is expressed as impedance seen by the relay. These series connected FACTS devices inject a series voltage with the line and change the line impedance. Hence, determining the boundaries of operation of a distance relay, in the presence of FACTS controllers, is a challenging task. In this paper an extended review is done to identify the impact of various series FACTS controllers on distance protection. © 2015 IEEE.